DETERMINAN KETERLIBATAN LANSIA DALAM PASAR KERJA DI KABUPATEN SRAGEN - Jihad Lukis Panjawa; Joko Triyanto (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2020)
The consequences of the increasing population become a dilemma in relation to the potential or challenge for national and regional development, such as increased life expectancy, increasing the number of elderly and dependency ratio. This research is objected to analyze the determinants of the elderly involvement in the job market. Case studies are conducted in Sragen Regency. Analysis tool used to answer research objectives using logit regression. It is a statistical analysis tool designed to measure the direction and magnitude of one or more variables to one or more dependent variables where the dependent variable is represented by a dummy variable. Dummy on the dependent variable is indicated by 1 as the elderly worker and 0 as other (leisure). The results showed that gender, head of the household relationship, marital status, education level and domicile had a significant effect on the decision of the elderly population to keep working or leisure time. Moreover, guarantees as measured by ownership of pension guarantees has no significant effect on the elderly's decision to work or leisure time.